2021
DOI: 10.1037/apl0000855
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety responses to the unfolding COVID-19 crisis: Patterns of change in the experience of prolonged exposure to stressors.

Abstract: An immense amount of work has investigated how adverse situations affect anxiety using chronic (i.e., average) or episodic conceptualizations. However, less attention has been paid to circumstances that unfold continuously over time, inhibiting theoretical testing and leading to possible erroneous conclusions about how stressors are dynamically appraised across time. Because stressor novelty, predictability, and patterns are central components of appraisal theories, we use the COVID-19 crisis as a context to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 83 publications
(128 reference statements)
1
72
0
Order By: Relevance
“…In particular, risk propension seemed to have increased in the comparison between the first and the second wave (GRISP: 26.93 in the first wave, 27.84 in the second). These results might suggest a habituation dynamic, in which a perpetual exposure to a risk tends to decrease the anxiety of people towards the risk [44,45], thus making people more inclined to take risks [46][47][48]. This can happen even when risk perception appears to have increased (Wilson probability: 6.68 in the first wave, 8.06 in the second), as habituation can be mediated by other factors like increased self-efficacy or locus of control [49,50].…”
Section: Discussionmentioning
confidence: 97%
“…In particular, risk propension seemed to have increased in the comparison between the first and the second wave (GRISP: 26.93 in the first wave, 27.84 in the second). These results might suggest a habituation dynamic, in which a perpetual exposure to a risk tends to decrease the anxiety of people towards the risk [44,45], thus making people more inclined to take risks [46][47][48]. This can happen even when risk perception appears to have increased (Wilson probability: 6.68 in the first wave, 8.06 in the second), as habituation can be mediated by other factors like increased self-efficacy or locus of control [49,50].…”
Section: Discussionmentioning
confidence: 97%
“…A multilevel confirmatory factor analysis was conducted on Amos 22.0 (Arbuckle, 2016) to assess the fit of our measurement model (Byrne, 2001; Fu et al , 2020). The analysis indicate that the five-factor model (proposed) fits reasonably well to the data with the RMSEA, relative chi-square and the CFI satisfying their criteria of <0.07 (MacCallum et al , 1996), <3 (Kline, 1998) and >0.90 (Awang, 2015), respectively, and NFI and GFI were >0.80 (Forza and Filippini, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have attempted to examine the impact of such a pandemic on the workplace and the employees (e.g., Caldas et al, 2020;Trougakos et al, 2020). For instance, a recent study by Fu et al (2021) found that the anxiety levels of the employees are affected by the reported number of COVID-19 cases and the acceleration and velocity at which the reported number is changing, thus affecting the employees' work functioning (engagement, performance, and emotional exhaustion). However, fewer studies have looked at what constitutes effective leadership in the workplace during such a crisis and its potential antecedents (e.g., Hu et al, 2020;Yuan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%